QTL for resistance to summer mortality and OsHV-1 load in the Pacific oyster (Crassostrea gigas) - Sauvage, Christopher; Boudry, Pierre; De Koning, D. -j.; Haley, C. S.; Heurtebise, Serge; Lapegue, Sylvie (Animal Genetics, 2010)
P>Summer mortality is a phenomenon severely affecting the aquaculture production of the Pacific oyster (Crassostrea gigas). Although its causal factors are complex, resistance to mortality has been described as a highly heritable trait, and several pathogens including the virus Ostreid Herpes virus type 1 (OsHV-1) have been associated with this phenomenon. A QTL analysis for survival of summer mortality and OsHV-1 load, estimated using real-time PCR, was performed using five F-2 full-sib families resulting from a divergent selection experiment for resistance to summer mortality. A consensus linkage map was built using 29 SNPs and 51 microsatellite markers. Five significant QTL were identified and assigned to linkage groups V, VI, VII and IX. Analysis of single full-sib families revealed differential QTL segregation between families. QTL for the two-recorded traits presented very similar locations, highlighting the interest of further study of their respective genetic controls. These QTL show substantial genetic variation in resistance to summer mortality, and present new opportunities for selection for resistance to OsHV-1.